EFFECT OF NATURAL FEEDING Daphnia sp. RESULTS OF DIFFERENT CULTURE MEDIA ON THE GROWTH AND SURVIVAL OF TILAPIA (Oreochromis niloticus) FRY - Damayanti, Riska Aulia; Mujtahidah, Tholibah; Sari, Annisa Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This study aims to determine the effect of giving Daphnia sp. the results of different culture media on the growth and survival of tilapia fish seeds. This research was conducted from November 2021 to January 2022. The method used in this study is the Complete Randomized Design (CRD) method with four treatments and three replicates, namely P1 (Daphnia sp. cabbage vegetable culture results), P2 (Daphnia sp. banana peel culture results), P3 (Daphnia sp. chicken egg culture results), and K (Control). The results showed the highest growth in the P3 treatment with a weight gain of 0.90 g and a length gain of 1.72 cm, followed by treatment P1 of 0.49 g with a length gain of 1.09 cm, and the lowest in the P2 treatment of 0.33 g with a length increase of 1.13 cm. The highest survival rate during rearing was found in the P3 treatment at 91.1%, and the lowest survival rate in the P1 and P2 treatments at 87.8%. Water quality parameters obtained were temperature ranging from 25 - 29o C, pH ranging from 7.32 - 8.56, DO ranging from 3.1 - 5.3 mg/l, and ammonia ranging from 0.15 - 0.25 mg/l.